(untitled) (The Lumbini Journal of Business and Economics, 2025)
Purpose: This study examines the impact of non-performing loans on the profitability of Nepalese Commercial Banks. Methods: The data were analyzed using a multiple regression, descriptive, and correlational model. Up until February 2024, the combined data of five commercial banks with the lowest paid-up capital out of the twenty commercial banks was examined. Return on equity and return on assets are the study’s dependent variables, while the capital adequacy ratio, non-performing loan ratio, cash reserve ratio, and bank size are its independent factors. Results: The results show that several financial metrics, including bank size, cash reserve ratio, non-performing loan ratio, and capital adequacy ratio, are important determinants of ROA and ROE. Highlighted are significant problems with non-performing loans and impairment expenses. Conclusion: Non-performing loans significantly impact bank profitability, as evidenced by their positive correlation with reduced returns on assets (ROA) and returns on equity (ROE). This underscores the importance of effective management and mitigation strategies for non-performing loans to safeguard the profitability and stability of banks in Nepal. Moreover, the analysis highlights the interconnectedness of various financial metrics with bank profitability.